Apakah Keadilan Organisasi Berperan dalam Menampilkan Perilaku Kerja Inovatif pada Karyawan Gen Z? - Alviyani, Ira; Etikariena, Arum (Jurnal Online Psikogenesis, 2025)
Innovation is important for the sustainability of the company, therefore innovative work behavior of employees is an important factor in Gen Z employees, who are known to be innovative. However, Gen Z employees often express disappointment over unfairness in the workplace, which is influenced by organizational justice. This study was conducted to see the role of organizational justice on innovative work behavior in Gen Z employees. Data were obtained from 217 employees aged 18-28 years using an online questionnaire. Based on the results of a simple linear regression analysis, organizational justice plays a positive and significant role in innovative work behavior (β = 0.36, p < .001). Organizational justice can explain 13% of the variance in innovative work behavior (R² = 0.13, p < .001). Based on the results of multiple linear regression analysis, the procedural justice dimension plays a positive and significant role in innovative work behavior (β = 0.40, p < .001). However, the dimensions of distributive justice (β = 0.08, p = .32), interpersonal justice (β = 0.07, p = .36), and informational justice (β = -0.08, p = .28) did not play a significant role in innovative work behavior. Research shows that procedural justice plays a role in encouraging innovative work behavior; therefore, companies must ensure a fair, transparent, and consistent decision-making process so that Gen Z employees exhibit innovative work behavior.